Aligning Climate Change and Sustainable Development Goals With an Innovation Systems Roadmap for Renewable Power - Hernandez, Rebecca R.; Jordaan, Sarah M.; Kaldunski, Ben; Kumar, Naresh (Frontiers in Sustainability, 2020)
Energy development improves quality of life for humans, but also incurs environmental consequences. Thus, a global energy transition from fossil fuels to renewable energy may mitigate climate change but may also undermine the capacity to achieve some or all 17 Sustainable Development Goals (SDGs). In this study, we use an innovation systems approach to construct a comprehensive roadmap for solar and wind energy to anticipate and improve impacts of a transition to a low carbon future in a manner ensuring climate goals and SDGs are mutually reinforcing. Our multidisciplinary approach began with an assessment of public investments in renewable energy followed by a two-day research prioritization workshop. Approximately 60 expert workshop participants identified six research themes that proactively address the environmental sustainability of renewable energy. Next, we identified linkages between the six research themes and all 17 SDGs. Finally, we conducted a scientiometric analysis to analyze the research maturity of these themes. The results of these efforts elucidated the limits of existing knowledge of renewable energy-SDG interactions, informing the development of a research, development, demonstration, and deployment (RD3) roadmap to a renewable energy future aligned with both climate goals and SDGs. The RD3 roadmap has been designed to systematically develop solutions for diverse actors and organizations. Overall, our findings confer a broad vision for a sustainable transition to renewables to minimize unintended environmental consequences and supporting interoperability among actors particularly poised to influence its magnitude and direction.